Suitability analysis on ovitrap installation site for dengue disease control - Kok, Suet Yheng 1987- , author 638433; Mohamad Nor Said, supervisor 516238; Fakulti Geoinformasi dan Harta Tanah 555724 (2011)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2011